Cardiovascular Risk of Synthetic, Non-Biologic Disease-Modifying Anti-Rheumatic Drugs (DMARDs) - Mourouzis, Iordanis S.; Manolis, Antonis S.; Pantos, Constantinos (Current Vascular Pharmacology, 2020)
Patients with rheumatoid diseases have an increased risk of cardiovascular disease (CVD) and CVD-related death compared with the general population. Both the traditional cardiovascular risk factors and systemic inflammation are contributors to this phenomenon. This review examines the available evidence about the effects of synthetic, non-biologic disease-modifying antirheumatic drugs (DMARDs) on CVD risk. This is an important issue for clinicians when deciding on individual treatment plans in patients with rheumatic diseases. Evidence suggests that synthetic, non-biologic DMARDs such as methotrexate, sulfasalazine, hydroxychloroquine, leflunomide and tofacitinib show decreased CVD morbidity and mortality. However, the strongest data in favour of a reduction in CVD events in rheumatoid patients are shown with methotrexate, which has been the focus of most studies. Adequate proof for a favourable effect also exists for hydroxychloroquine. Larger, prospective studies and randomized clinical trials are needed to better characterize the effect of synthetic, non-biologic DMARDs on CVD outcomes in these patients. Design of future studies should include areas with lack of evidence, such as the risk for heart failure, arrhythmias and valvular heart disease. The clinically relevant question whether synthetic, non-biologic DMARDs are inferior to biologic DMARDs in terms of CVD outcomes remains not adequately addressed.
Keywords: leflunomide